2009
DOI: 10.1177/1010539509338730
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated With Cigarette Smoking Among University Students: A Study From Iran

Abstract: To determine the prevalence of cigarette use among college students and to identify correlates of cigarette smoking, a cross-sectional study was conducted on 1750 college students in the city of Kerman, located in southern Iran. The average age of college students was 21.2 ± 2.1 years. A total of 52% participants were female, 92% were single, and 11% (184) were smokers (22% of men and 2.4% of women). The average age of smoking initiation was 15.9 ± 4.5 years. A high association was shown with the use of cigare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 18 publications
4
20
1
Order By: Relevance
“…Previous studies in other cities of Iran revealed that prevalence of smoking was 9%, 6%, 11% and 7.4% in Shiraz, Golestan, Kerman and Ardabil Universities of Medical Sciences, respectively (13)(14)(15)(16). Therefore, it seems that the prevalence of smoking among Iranian health professional students is approximately in the range of 6% to 11%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in other cities of Iran revealed that prevalence of smoking was 9%, 6%, 11% and 7.4% in Shiraz, Golestan, Kerman and Ardabil Universities of Medical Sciences, respectively (13)(14)(15)(16). Therefore, it seems that the prevalence of smoking among Iranian health professional students is approximately in the range of 6% to 11%.…”
Section: Discussionmentioning
confidence: 99%
“…Among 1.2 billion smokers of the world, 800 million live in developing countries and cigarette smoking is rapidly spreading among adolescents (Karimy et al, 2012); for this reason, a developing country was chosen for this study. Between 2002 and2030, it is estimated that cigarette induced death rates in developed countries will increase by 9%, while in developing countries this rate will be doubled (Nakhaee et al, 2011). According to the World Health Organization, in 2015, cigarettes will cause 50% more deaths than HIV/AIDS virus and, basically, 10% of deaths around the world will be connected to this behaviour (Nakhaee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Between 2002 and2030, it is estimated that cigarette induced death rates in developed countries will increase by 9%, while in developing countries this rate will be doubled (Nakhaee et al, 2011). According to the World Health Organization, in 2015, cigarettes will cause 50% more deaths than HIV/AIDS virus and, basically, 10% of deaths around the world will be connected to this behaviour (Nakhaee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many international studies have shown that about 85 to 90% of heavy smokers start smoking before the age of 20 (Nakhaee, Divsalar, & Bahreinifar, 2011;Pouresmlami, 2008). More than one-third of those who experienced smoking before the age of 18 will become daily and about two-thirds of them will become regular smokers (Centers for Disease Control and Prevention, 2000;Ramezankhani, Sarbandi, & Masjedi, 2010;Sally, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other addictives, cigarettes are more available. Thus, cigarette use among adolescents needs to be taken into account and studied (Mee, 2009;Nakhaee & Divsalar, 2009;Ramezankhani, Sarbandi, & Masjedi, 2010;Rigotti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%